2011
DOI: 10.1177/1740774511402526
|View full text |Cite|
|
Sign up to set email alerts
|

How to use marginal structural models in randomized trials to estimate the natural direct and indirect effects of therapies mediated by causal intermediates

Abstract: Background Although intention-to-treat analysis is a standard approach, additional

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Mediation analyses seek a more in-depth understanding by decomposing the intention-to-treat effect into a direct and indirect effect, mediated by given intermediaries [1]. For instance, Oba et al [2] contrasted two treatments that equally suppressed the incidence of cardiovascular events but had a small but significantly different effect on systolic blood pressure. A mediation analysis provided a more in-depth understanding by clarifying what the (relative) treatment effect would be if an effect on systolic blood pressure could be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Mediation analyses seek a more in-depth understanding by decomposing the intention-to-treat effect into a direct and indirect effect, mediated by given intermediaries [1]. For instance, Oba et al [2] contrasted two treatments that equally suppressed the incidence of cardiovascular events but had a small but significantly different effect on systolic blood pressure. A mediation analysis provided a more in-depth understanding by clarifying what the (relative) treatment effect would be if an effect on systolic blood pressure could be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the sequential g‐estimation method of SNMMs, the inverse‐probability weighted estimation of MSMs and g‐computation with Monte Carlo simulations after fitting the parametric models of each variable's conditional distribution using maximum likelihood methods (parametric g‐formula) may also be readily applicable methods for estimating controlled direct effects using standard software. Yet SNMMs , MSMs , and g‐formula differ in causal parameters that analysts target for and in their modeling assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Although these methods have been originally intended to cope with longitudinal settings where treatment changes during the follow‐up period and intermediate variables also change over time, most studies demonstrated these methods on point‐treatment or point‐intermediate situations or both . In the presence of repeated measures data, treatment itself is likely to be confounded by covariates that are affected by prior treatment, which results in a time‐dependent confounding problem .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that LDL levels lower than target values could reduce both cardiovascular events (HR = 0.72, 95% CI = 0.48-1.06, P = 0.10) and diabetes-related events (HR = 0.82, 95% CI = 0.58-1.17, P = 0.29) independently of atorvastatin, which might show the presence of an LDL-loweringmediated effect of atorvastatin. Formal statistical assessment as to atorvastatin's cholesterol-lowering-mediated effects is the subject of future work, which might be carried out using the marginal structural models 33,34 or the structural nested models. 35,36 Several studies have reported the possibility that statins might increase diabetic risk by increasing blood glucose levels.…”
mentioning
confidence: 99%